Root Anatomy and Canal Configuration of Maxillary Molars in a Brazilian Subpopulation: A 125-μm Cone-Beam Computed Tomographic Study - Mohara, Nelson Tsutomu; Coelho, Marcelo Santos; de Queiroz, Nathalia Valle; Borreau, Marcelle Louise Sposito; Nishioka, Marko Massao; de Jesus Soares, Adriana; Frozoni, Marcos (European Journal of Dentistry, 2019)
Objective Knowledge of internal anatomy of the teeth is of great importance in endodontics, leading to success in root canal therapy (RCT). The aim of this study was to assess the root anatomy and canal configuration of maxillary molars in a Brazilian subpopulation using tomographic images using a voxel size of 125 μm.Materials and Methods This in vivo retrospective study assessed 651 cone-beam computed tomographic scans from 328 maxillary first molars and 323 maxillary second molars. The images were assessed by two endodontists and an oral radiologist. Only permanent molars with fully developed roots and with no signs of RCT were included.Results Maxillary first and second molars presented three separated roots in 99.39 and 90.09% of the cases, respectively. The presence of mesiolingual canals in the mesiobuccal roots was 64.22% for maxillary first molars and 33.56% for maxillary second molars. Distobuccal canals in the maxillary first and second molars presented Vertucci's Type I configuration in 99.39 and 99.66%, respectively, and palatal canals in the maxillary first and second molars presented Vertucci's Type I configuration in 99.69 and 99.68%, respectively. Maxillary second molars were more subjected to anatomical variations than first molars. Female patients presented higher prevalence of mesiolingual canals in the maxillary second molars.Conclusions The most prevalent morphology in the maxillary first and second molars was three root canals. The presence of only one or two roots is more likely to occur in the maxillary second molars than in the maxillary first molars. Mesiolingual canals in mesiobuccal roots are more frequent in the maxillary first molars than in the maxillary second molars, and the occurrence of two distobuccal or two palatal canals is rare.
Keywords: canal configuration; cone-beam computed tomography; maxillary molars; morphology; root anatomy; root canal therapy